أثر المازني فيمن جاء بعده (المبرّد ـ الفارسي ) - عوض, سامي; سلوم, صفوان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
أبو عثمان المازني، أستاذ المبرّد، وقد عدّ إمام عصره في النحو واللغة، نهل معارفه من كبار العلماء البصريين حتى فاقهم علماً، وقد ساعد على نبوغه قوّة بيانه وبلاغته. وتميّز المازني بآرائه المتفرّدة التي تعكس رؤيته العميقة وثقافته الموسوعية. ولعلّ كتابه " التصريف " يعدّ أوّل كتاب مستقلّ في الصرف، دون أن يعني ذلك فصل الصّرف عن النّحو. وقد جمع فيه المازني مباحث التّصريف على نحوٍ مستقلٍّ، مستعيناً بكثير من آراء الخليل وسيبويه والأخفش، مستمداً مادته الصرفيّة من الأصول النظرية التي بنى عليه العلماء الأوائل مادّتهم الصرفيّة، فمهّد الطريق لمن جاء بعده، لينتهجوا نهجه في تأليف كتب مستقلّة في الصّرف، ويتبنّوا كثيراً من آرائه المستقلّة وأقيسته الخاصّة. Abo Othman AL-Mazni is Baker bin Mouhammad bin Bbkiah، teacher of AL-Mobarred. He was regarded as the leader of his time in grammar and morphology. He acquired his lores from the famous Basrien scholars، until he exceeded them, and what helped his genius was his strong declaration and eloquence. Al-mazni was known for his unique thoughts which reflected his independence، and encyclopedic culture. His book Morphology may be the first real invitation from a scholar to separate grammer from morphology. Al-mazni has gathered in it morphological research independently, getting help from the ideas of Alkhalil، Sepuah، Alakhfash and others. Following dialectical style، the telling philosophy obviously found in it، was derived from the theoretical principles on which the premier scholars based their morphological subject. So، Al-mazni paved the way to his followers of scholars، they adopted his style in separating grammar from morphology and many of his independent thoughts and unique positions.